SAMHD1 as the Potential Link Between SARS-CoV-2 Infection and Neurological Complications - Khan, Aiza; Sergi, Consolato (Frontiers in Neurology, 2020)
The recent outbreak of coronavirus infectious disease 2019 (COVID19) caused by SARS-CoV-2 has rapidly spread around the globe, generating in severe events an acute, highly lethal pneumonia and death. In the past two previously similar CoVs, the severe acute respiratory syndrome CoV (SARS‐CoV-1) and Middle East respiratory syndrome CoV (MERS‐CoV) also gained global attention as they produced clinical symptoms similar to those of SARS-CoV-2 utilizing angiotensin-converting enzyme 2 (ACE2) receptor to enter inside the cells. COVID-19 may also present with neurological symptoms. The proper understanding of the expression and distribution of ACE2 in central and peripheral nerve systems is crucial to understand better the neurological morbidity caused by COVID-19. Using the bioinformatic tool STRING and references through text mining tools associated with Coronaviruses, we identified SAMHD1 as the probable link to neurological symptoms. Compared to the response to influenza A virus and respiratory syncytial virus, SARS-CoV-2 evokes a response that lacks robust induction of a subset of cytokines, including the Type I and Type III interferons as well as a few chemokines. We correlate ACE2 to the pathogenesis and neurologic complications of COVID-19 and found that SAMHD1 links to the NF-κB pathway. No correlation was found with other molecules associated with Coronavirus infection, including ADAR, BST2, IRF3, IFITM3, ISG15, MX1, MX2, RNASEL, RSAD2, and VPRBP. We suggest that SAMHD1 is the molecule that may be behind the mechanisms of the neurological complications associated with COVID-19.